If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6t + -3 + 2t = 29 Reorder the terms: -3 + 6t + 2t = 29 Combine like terms: 6t + 2t = 8t -3 + 8t = 29 Solving -3 + 8t = 29 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 8t = 29 + 3 Combine like terms: -3 + 3 = 0 0 + 8t = 29 + 3 8t = 29 + 3 Combine like terms: 29 + 3 = 32 8t = 32 Divide each side by '8'. t = 4 Simplifying t = 4
| -6(x+3)+4x+7=6x+8 | | T=4U/E | | -3-p=5p+21 | | X^2-3ax+2a^2+3a-9=0 | | 5a+b=cfora | | T=AB-2 | | 9x-8+9x=7x+16 | | -x+4x+6=14-2 | | 58a+b=cfora | | 13x-3=5x | | 2b-3+6-8=1-b | | x/(x+1)+x/(x-1)=0 | | 2x/5+3=101/2 | | 4m-y=nform | | 12+4x=8x-8 | | 1/2(8-6h)=5 | | 3x^2-12x+24y-48=0 | | 6-4x=7x-9x+4+2 | | C=15f+8h+5p | | 27x-2+47=180 | | 4z+6z=10 | | 27x-2=47 | | 4(x-3)+2=26 | | 7m+n=2forn | | 16x-8=14x+8 | | -3-(2-3x)=2x-(5-x) | | (3x-c)-5=x-7 | | 13-2n=-37 | | a+b(x-y)=cforx | | 20x+10=50 | | 2(x+4)-5(2x-1)= | | 11x-3=10x+5 |